IoT-enabled farms and climate-adaptive agriculture technologies: Investment lessons from Singapore - Montesclaros, Jose Ma. Luis; Babu, Suresh Chandra; Teng, Paul S. (International Food Policy Research Institute, 2019)
The adoption of climate-adaptive agricultural technologies (CAATs) for extensive (outdoor) agriculture is stalled by funding gaps experienced by governments in the Mekong countries, with negative implications on the rural farming industry, on income and job security among smallholder farmers, and on food sufficiency and access across the population. We argue that one way of helping bridge these gaps is for providers and users of CAATs for extensive agriculture to learn from the practices of those in CAATs for intensive (indoor) agriculture. Indoor CAATs are already receiving significant private-sector investment, a key reason being their ability to leverage the complementary nature of these technologies within farms that are integrated and enabled to use the so-called Internet of things (IoT). Seamlessly linking different CAATs (sensors, crop analytics, and automation) can allow for synergies that significantly boost crop yields and, in turn, the viability of investing in CAATs. We demonstrate these synergies through two case studies, one that looks at the increasing global investment in indoor CAATs and another that describes a financial viability assessment for an indoor farm in Singapore. We conclude with lessons on how these insights can be transferred to the Mekong countries, including a prototype IoT-enabled extensive farm that integrates multiple CAATs, and an investment assessment tool for translating the yield benefits into terms that investors can appreciate.